Toxicity analysis of three different essential (clove, taramira & neem oil) against sugarcane black bug (Cavelerius excavatus) - Tayyab Abbas, Muhammad; Zeeshan khalid, Muhammad; Nauman, Huzaifa; Azad, Rashid; Ali, Farman; Hussain, Arjad; Naeem, Muhammad; Shafiq, Nabeel; Faizan, Muhammad; Zaib Noor, Shah; Aziz Ul Ghaffar, Muhammad Zahid; Saeed, Rabia (Journal of Agriculture and Biology, 2025)
Sugarcane is a significant industrial cash crop that accounts for almost 80% of the world's sugar production, sugarcane is also very important economically in Pakistan. Sugarcane black bug is one of the sucking pest of sugarcane crop and creating significant yield and quality losses. Although conventional chemical pesticides are effective, their misuse contamination endanger human health, soil biology, and the environment. Naturally derived biopesticides offer a safer and more sustainable alternative. This study evaluated the efficacy of neem, clove, and taramira oils against sugarcane black bug nymphs using a leaf-dip bioassay. Numbers of dead individuals were recorded daily till seven days. The findings demonstrated that clove oil had the best and fastest insecticidal effect, resulting in 93.3% death after 24 hours at 4 ppm and attaining total mortality within 48 hours, despite continuously low LC50 values. Neem oil showed mild but long-lasting effects, but taramira oil acted more slowly and took longer to reach full efficacy. While neem and taramira oils would be better suited for long-term or preventative management strategies, clove oil ultimately showed the most potential for rapid insect control.
Keywords: Biopesticides; Essential oils; Sugarcane black bug; Insecticidal activity; pest management; Sustainable